Epidemiology and control of tuberculosis in the Western Pacific Region: update with 2013 case notification data - Tom Hiatt; Nobuyuki Nishikiori (World Health Organization Regional Office for the Western Pacific, 2016)
Introduction: Since the year 2000, tuberculosis (TB) prevalence in the World Health Organization (WHO) Western Pacific Region decreased 36%. However, there were an estimated 1.6 million TB cases in the Region in 2013. This study describes a regional analysis using the WHO global TB database data from 2000 to 2013. Methods: TB surveillance data are annually collected from 36 countries and areas in the Western Pacific Region using a web-based system. TB case notifications, treatment outcomes and information on TB/HIV coinfection are analysed descriptively. Stratified analysis of the TB data by age, sex and countries and areas were conducted. Results: Countries and areas in the Western Pacific Region notified 1.3 million new and relapse TB cases in 2013. TB notification rate increased in the early 2000s, stabilized for several years and declined recently. Country-specific TB notification rates declined over time for all age groups in most countries. TB treatment success rates remain high in the Region with 16 countries reaching or maintaining 85% (or higher) in 2013. HIV testing among TB cases has increased gradually with approximately 11 000 HIV-positive TB cases diagnosed each year since 2009. Discussion: The results suggest that true TB incidence is possibly declining. Treatment success rates have remained high for six of seven high-burden countries. TB surveillance data analysis is an important source of programmatic and epidemiological information. Careful interpretation of these findings can provide useful insight for programmatic decision-making. While the TB burden remains immense, national TB programmes must evolve and adapt to build upon previous efforts.